Monetary policy rules and macroeconomic stability: Some new evidence. - Mavroeidis, S (AEA, 2010)
I revisit the question of indeterminacy in US monetary policy using limited-information identification-robust methods. I find that the conclusions of Clarida, Galí, and Gernter (2000) that policy was inactive before 1979 are robust, but the evidence over the Volcker-Greenspan periods is inconclusive. I show that this is in fact consistent with policy being active over that period. Problems of identification also arise because policy reaction has been more gradual recently. At a methodological level, the paper demonstrates that identification issues should be taken seriously, and that identification-robust methods can be informative even when they produce wide confidence sets.